Freie Zeit: Eine politische Idee von der Antike bis zur Digitalisierung - Ritschel, Gregor (transcript, 2021)
"The realm of freedom actually begins only where labour which is determined by necessity and mundane considerations ceases" - Karl Marx once said. And today? Despite extensive automatisation, the norm of full-time work remains. The motto "social is what creates work" is supported by almost all political actors. At the same time, the previous form of a full-time working society is becoming more fragile and unequal: the care crisis, the gender pay gap, precarious jobs or unregulated crowdwork on digital platforms reveal just a few of the many yield lines. Considering the history of political ideas on free time and the current debates on automatisation and digitalisation, Gregor Ritschel drafts a plea for a gradual exit from the previous working society into a "multi-activity society" (André Gorz). He reveals that shortening working hours can enable us to create a more social, more creative and also more environmentally friendly world.